DEVELOPING LEADERSHIP IN STUDENTS THROUGH PROBLEMATIC SITUATIONS AND DECISION-MAKING SKILLS (Eureka Journal of Language, Culture & Social Change, 2026)
The development of leadership skills in students through problematic situations and decision-making is a pressing task in modern pedagogy. In the 21st century, academic and social success depends on responsible decision-making and leadership competencies. Problem-based approaches enable students to analyze conditions, generate alternative solutions, and select the most effective decisions, fostering independent thinking, responsibility, and creativity. Pedagogical methods such as problem-based learning, group work, interactive methods, didactic games, simulations, project-based learning, and reflective practices provide practical opportunities for students to practice leadership. This approach not only strengthens cognitive, social, and emotional development but also prepares students for real-life situations. The study presents practical examples of applying these methods and highlights their effectiveness in forming leadership skills in students.
Keywords: Leadership development, Problem-based learning, Decision-making skills, Independent thinking, Pedagogical methods, Student engagement, Reflective practice.